Piroxicam Percutaneous Permeation from Gels Through Membrane Models of Shed Snakeskin and Cellulose - Anis Yohana Chaerunisaa; Marline Abdassah; Jutti Levita; Ellin Febrina; Ulfinana Hafni (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Skin has a very important role in determining percutaneous absorption of active substance in topical administration. Study on percutaneous permeation of piroxicam from gel had been conducted using Franz Diffusion Cell with membrane model of shed snakeskin and cellulose. Piroxicam gels were made using Aqupec HV-505 base with 0; 2.5; 5; and 7.5% of DMSO as an enhancer. The results showed that the most stable gel preparation was the one with 5% DMSO (F2), so it was used for further investigation to which percutaneous permeation test. The permeation test was conducted in preparation without and with 5% DMSO (F2) in vitro through shed snakeskin and cellulose membranes. The results showed that F2 increased the permeation rate by as much as 0.0281% per minute. In comparison, the permeation rate of formulation without DMSO (F0) was 0.012% per minute. It can be concluded that DMSO can increase piroxicam penetration through shed snakeskin. Permeation study using cellulose membrane on formula F2 revealed permeation rate as much as 0.006% per minute whereas that without DMSO (F0) was 0.0112% per minute.Keywords: DMSO, cellulose membrane, percutaneous permeation, piroxicam, shed snakeskin.